Development of Multimedia-Based E-Learning Models in Distance Learning Concepts - Cantika, Nourma Islam Dewi; Bastian, Hanafi Dana (Journal of Multimedia Trend and Technology, 2025)
Learning content is the most important thing in the teaching and learning process. In the distance learning model, content must receive important attention, because in distance learning, students get material with a greater proportion of reading content independently than face to face with the tutor. Moreover, currently the type of learning can be said to be developing with the help of information technology. The problem lies in the type of each person in implementing learning styles. Not everyone has a type as an active reader. The application of multimedia to distance learning content will help students absorb more learning materials. The method used is blended learning which combines conventional concepts with information technology to change the concept of learning to be more interactive. This is proven by the increase in learning outcomes of students who study using the blended learning concept using multimedia compared to those who study independently. In the current situation, namely the era of personalized learning, multimedia plays a very important role in the implementation of teaching and learning.